Explaining Forward Exchange Bias...Intraday - Lyons, Richard K.; Rose, Andrew K. (Journal of Finance, 1995)
Intraday interest rates are zero.Consequently, a foreign exchange dealer can short a vulnerable currency in the morning, close this position in the afternoon, and never face an interest cost.This tactic might seem especially attractive in times of crisis, since it suggests an immunity to the central bank's interest rate defense.In equilibrium, however, buyers of the vulnerable currency must be compensated on average with an intraday capital gain as long as no devaluation occurs.That is, currencies under attack should typically appreciate intraday.Using data on intraday exchange rate changes within the EMS, we find this prediction is borne out.